BIG DATA & KNOWLEDGE MANAGEMENTENDEAVOR: MyAlumni UiTM - AN ACTIVE ENGAGEMENT PLATFORM INITIATIVES - Roziya Abu; Ainul Azreen Adam; Nazura Mohamed Sayuti; Mohamad Razeef Shah Mohmad Rafik (Prosiding International conference on Information Technology and Business (ICITB), 2020)
UniversitiTeknologi MARA (UiTM) was established in 1956 as Dewan Latehan RIDA and has open its doors to more than 50 students with a focus to help the Malays in rural areas. Since then, the Dewan Latehan RIDAnow known as UniversitiTeknologi MARA (UiTM) has started to grow into the largest higher e/ducation institution in Malaysia in terms of its physical infrastructure, staff organization and student registration. UiTM alumni include individuals from all walks of life in Malaysia. With a total of more than 800 thousand graduates, the number of UiTM Alumni is the largest in Malaysia and one of the largest in the world. UiTM's electronic database system (known as eAlumni) only started in 2006 and almost 300 thousand alumni data are still in the process of migrating from personal files to electronics version. Realizing the difficulties in this migration work process, Alumni Network Center, ICAN UiTM, has put an initiative to introduce MyAlumni UiTM. MyAlumni UiTM is the latest addition feature of the eAlumni UiTM database system. It is an interactive medium that aims to create interaction and engagement among UiTM alumni partners as well as help UiTM identify active alumni. MyAlumni UiTM is managed by the Data Unit, UiTM Alumni Network Center, ICAN in collaboration with the Infostructure Department, PPII. This article will share details of work processes and initiatives carried out by ANC, ICAN UiTM in an effort to ensure the existence of engagement and empowering of UiTM Alumni.Keywords: Alumni Data, Big Data, Alumni Engagement, Alumni Information Technology, Knowledge Management